The relevance of connected car features on brand loyalty and customer satisfaction - Noronha, Madalena Lobo Antunes de Matos e (2024)
Every day, we are becoming more connected. Our phones have become the ultimate connectivity device, and soon, the car will follow in the same footsteps. The future car will be more sophisticated and tailored to consumers, becoming an extension of our smartphones. Connectivity will be an essential source of value creation for brands, as it may generate revenue, optimise costs, and overall increase and improve the driver experience. This dissertation explores the relevance of connected car features to brand loyalty and customer satisfaction. An extensive literature review was performed to gain knowledge on the topic. Both qualitative and quantitative research were conducted to answer the research question. For the qualitative research, in-depth interviews were conducted. The study aimed to gain insights into the motivations, habits, and attitudes behind purchasing a vehicle and comprehend the role of connected car features in the purchase process. For the quantitative research, an online survey was formulated. The questions focused on the motivations and habits towards purchasing a car, followed by the general perceptions of connectivity features. Most questions used were statements using a 5-point Likert scale regarding the level of importance or agreement with the statement. The data collected from the research was then imported into the statistical program SPSS and analysed. Along with an analysis of the data, hypothesis testing was also used. From the study of the research conducted, both qualitative and quantitative, it was possible to conclude that connected car features do have a positive impact on customer satisfaction.